2019
DOI: 10.4314/ijbcs.v13i4.32
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of cyanobacterial strains isolated from different Tunisian inland waters: therapeutical and nutritional potential

Abstract: The last decade period has been characterized by a remarkable increase in the need for food, bioenergy, and pharmaceutical compounds. Meanwhile, microalgae have been in the center of interest as a rich and sustainable source of highly valuable natural products and bioactive compounds. In this perspective, the present study aimed at investigating the biochemical composition of 10 cyanobacterial strains collected from several Tunisian inland waters, seeking to identify the possible use of cyanobacteria in nutrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…12 Antioxidants in the alga could be responsible for the improved reproduction performances and these agreed with previous reports exploring effect of supplemental antioxidant-rich micro-alga intake on the reproduction performance of rats which concluded that the gestational intake of the antioxidant-rich micro-alga could lead to improved gestation outcome performances. 22 The free radical scavenging power of the micro-alga could be attributed to improved reproductive outcomes because of the reduction in the accumulated malondialdehyde observed in the supplemented group which was also similar to reports of of some researchers which described malondialdehyde as a compound of reproduction risk because of its negative effect on gestation. 23 Therefore, the reduction of this compound in the supplemented group of this study suggests that Chlorella vulgaris intakes due to its antioxidant properties could serve as a health promoter during the gestation period.…”
Section: Discussionsupporting
confidence: 87%
“…12 Antioxidants in the alga could be responsible for the improved reproduction performances and these agreed with previous reports exploring effect of supplemental antioxidant-rich micro-alga intake on the reproduction performance of rats which concluded that the gestational intake of the antioxidant-rich micro-alga could lead to improved gestation outcome performances. 22 The free radical scavenging power of the micro-alga could be attributed to improved reproductive outcomes because of the reduction in the accumulated malondialdehyde observed in the supplemented group which was also similar to reports of of some researchers which described malondialdehyde as a compound of reproduction risk because of its negative effect on gestation. 23 Therefore, the reduction of this compound in the supplemented group of this study suggests that Chlorella vulgaris intakes due to its antioxidant properties could serve as a health promoter during the gestation period.…”
Section: Discussionsupporting
confidence: 87%
“…The test isolate of Leptolyngbya valderiana is rich in protein content and has trivial application in the nutraceutical, cosmetic and pharmaceutical industries. 19…”
Section: Estimation Of Proteinsmentioning
confidence: 99%
“…The high content of carbohydrates is associated with the mucilaginous sheath in Leptolyngbya valderiana. 19 The carbohydrates help in skin lubrication thus keep the skin smooth and moist. They also act as viscosity boosters and thickening agents in skincare products.…”
Section: Estimation Of Carbohydratesmentioning
confidence: 99%